LOCAL GENIUS AS SOCIO-CULTURAL CAPITAL FOR EMPOWERING THE BAJO ETHNIC PEOPLE RESIDING AT THE COASTAL AREA OF BUNGIN PERMAI VILLAGE, SOUTH EAST SULAWESI - Ali Basri, La Ode; Parimartha, I Gde; Ardika, I Wayan; Meko Mbete, Aron (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2011)
In this dissertation the local genius as socio-cultural capital for empowering theBajo ethnic people residing at the costal area of Bungin Permai Village, TinanggeaDistrict, South Konawe Regency, South Sulawesi Province is discussed. The Bajo ethnicpeople have a set of local genius within their socio-cultural system which is reflected intheir belief, tradition and custom and is used as the reference for conceiving andexplaining the objective and essence of life and the world. However, such local geniushas not functioned optimally yet as they are still marginalized.This research is focused on (1) what forms of local genius serve as the sociocultural capital for empowering the Bajo ethnic group residing at the coastal area?; (2)how the local genius is developed to empower the Bajo ethnic people residing at thecoastal area?; and (3) what factors which may support and obstruct the local genius usedas the socio cultural capital for empowering the Bajo ethnic people residing at the coastalarea? Qualitative method is employed in this study with the approach of cultural studies.The theories used are the post colonial theory, structural theory, generative theory,hegemony theory and semiotic theory. The techniques used for collecting the data neededare participative observation, in-depth interview, library research, and focus groupdiscussion. The data obtained are analytically and descriptively processed and arepresented in the forms of narration, tables and visual illustration.The results of the study show that the Bajo ethnic people residing at BunginPermai Village have a set of local genius which may be potentially used as the sociocultural capital for empowering their community such as (1) indigenous skills andknowledge; (2) working culture; and (3) local organizations. The development of theindigenous skills and knowledge (pengetahuan dan ketrampilan asli; hereon abbreviatedto PKA) and the revitalization of their local organizations may be used as the sociocultural capital for empowering their community. The factors supporting the local geniusused as the socio cultural capital to support the empowerment of the Bajo ethnic peopleresiding at the coastal area are (1) availability of marine resources around the area where they live; (2) the existence of their local organizations; (3) being supporting by thecommunity and the government. The factors obstructing the local genius used as thesocio cultural capital to support the empowerment of the Bajo ethnic people residing atthe coastal area are (1) capitalistic economic transformation taking place within theircommunity; (2) collision against the mainland community with regard to cultural values;(3) low quality human resources; (4) negative image of the Bajo community. Themeanings of the local genius as the socio cultural capital for empowering the communityare (1) cultural preservation; (2) community empowerment and independence.